Medos vivenciados pelo lobo em contos tradicionais e renovados - Carra, Daniele da Silva (My University, 2025)
Fear, when it emerges on the pages of literature, is not merely an obstacle to be overcome by the characters; it is also a mirror, a crossroads, a passage. It forces confrontation with fragilities, demands difficult choices, reveals what was previously hidden beneath the surface. The way a character relates to this emotion, whether they surrender to it, challenge it, or are transformed by it, illuminates essential aspects of their subjectivity, tracing paths that transcend the plot and touch the symbolic dimension of existence. Based on this premise, this dissertation aims to investigate how fear is experienced and represented by the character Wolf in different children?s narratives. The analysis focuses on four works: "Little Red Riding Hood," by Charles Perrault; "The Three Little Pigs," by Joseph Jacobs; "Who's Afraid of the Big Bad Wolf?" by Silvana Menezes; and "The Girl and the Wolf," by Fábio Yabu. Throughout the work, this study aimed to: understand the specificities of traditional and contemporary tales (Ceciliato, 2008; Coelho, 2000, 2012; Propp, 2001); trace the symbolic trajectory of the Wolf in literature (Jesse, 2000; Silva, n/d; Hueck, 2016); reflect on the presence of fear as a founding element in literary narratives (Bauman, 2008; Delumeau, 2009; França, 2011, 2017; Roas, 2014); and conduct a close reading of the selected works (Perrault, 2012; Jacobs, 2006, 2021; Menezes, 2009; Yabu, 2014). The adopted methodology combined bibliographic research and literary analysis, enabling the intertwining of theory, critique, and reader sensitivity. The results point to a significant shift in how the character Wolf is depicted over time. While in classical narratives he appears as a feared, impenetrable, and immoral figure, in contemporary reinterpretations what emerges is a Wolf with psychological depth, vulnerable, often wrestling with his own fears. This change signals an expansion of meanings: what was once a symbol of threat becomes a metaphor for the human condition and its abysses. By analyzing these different representations, the research highlights how fear, previously projected solely onto the other, now also resides within the monster itself, shifting the perspective and redefining the figure of the Wolf in children's and young adult narratives. [resumo fornecido pelo autor]
O medo, quando emerge nas páginas da literatura, não é apenas um obstáculo a ser vencido pelos personagens, é também um espelho, uma encruzilhada, uma travessia. Ele força o confronto com fragilidades, convoca escolhas difíceis, revela aquilo que antes se ocultava sob a superfície. A forma como um personagem se relaciona com esse sentimento, se cede a ele, se o desafia ou se transforma a partir dele, ilumina aspectos essenciais de sua subjetividade, traçando percursos que vão além do enredo e tocam a dimensão simbólica da existência. Com base nessa premissa, a presente dissertação se propõe a investigar como o medo é vivenciado e representado pelo personagem Lobo em diferentes narrativas infantis. A análise recai sobre quatro obras: "Chapeuzinho Vermelho", de Charles Perrault; "A História dos Três Porquinhos", de Joseph Jacobs; De Quem Tem Medo o Lobo Mau?, de Silvana Menezes; e "A Menina e o Lobo", de Fábio Yabu. Ao longo do trabalho, buscou-se: compreender as especificidades dos contos tradicionais e contemporâneos Ceciliato, 2008; Coelho, 2000, 2012; Propp, 2001); traçar o percurso simbólico do Lobo na literatura (Jesse, 2000; Silva, s/d; Hueck, 2016); refletir sobre a presença do medo como elemento fundante nas narrativas literárias (Bauman, 2008; Delumeau, 2009; França, 2011, 2017; Roas, 2014); e realizar uma leitura atenta das obras selecionadas (Perrault, 2012; Jacobs, 2006, 2021; Menezes, 2009; Yabu, 2014). A metodologia adotada articulou pesquisa bibliográfica e análise literária, possibilitando entrelaçar teoria, crítica e sensibilidade leitora. Os resultados apontam para uma inflexão significativa na forma como o personagem Lobo é representado ao longo do tempo. Se nas narrativas clássicas ele aparece como figura temida, impenetrável e imoral, nas releituras contemporâneas o que emerge é um Lobo com densidade psíquica, vulnerável, muitas vezes às voltas com seus próprios medos. Essa mudança aponta para uma ampliação de sentidos: o que antes era símbolo de ameaça se transforma em metáfora do humano, e de seus abismos. Ao analisar essas diferentes representações, a pesquisa evidencia como o medo, antes projetado unicamente no outro, agora também habita o próprio monstro, deslocando o olhar e ressignificando a figura do Lobo nas narrativas infantis e juvenis. [resumo fornecido pelo autor]
Keywords: Análise do discurso literário; Personagens literários; Medo na literatura; Lobos na literatura; Literatura infantojuvenil; Discourse analysis, Literary; Characters and characteristics in literature; Fear in literature; Wolves in literature; Children's literature